Brief Strategic Therapy for Bulimia Nervosa and Binge Eating Disorder: A Clinical and Research Protocol - Pietrabissa, Giada; Castelnuovo, Gianluca; Jackson, Jeffrey B.; Rossi, Alessandro; Manzoni, Gian Mauro; Gibson, Padraic (Frontiers in Psychology, 2019)
Background: although cognitive behavioural therapy is the gold standard treatments for bulimia nervosa (BN) and binge eating disorder (BED), evidence for its long-term efficacy is weak. Empirical research support the efficacy of brief strategic therapy (BST) in treating BN and BED symptoms, but its statistical significance still need to be investigated. Objective: to statistically test the long-term efficacy of the BST treatment protocols for BN and BED through one-year post-treatment. Methods: a two-group longitudinal study will be conducted. Participants will be sequentially recruited for inclusion in a state-funded community psychotherapy clinic. Multilevel growth curve modeling will be used to estimate the average growth trajectories from baseline to one year after treatment termination for the severity of the BN and BED features as measured by the Eating Disorder Examination Questionnaire. Discussion: findings from this study will clarify the impact of BST in treating BN and BED symtoms. Conclusions: translating research into practice may inform how to ensure high-quality patient care.